Experimental investigation of spontaneous imbibition process of nanofluid in ultralow permeable reservoir with nuclear magnetic resonance. (29th June 2019) - Zhou, Hongda; Zhang, Qingsheng; Dai, Caili; Li, Yuyang; Lv, Wenjiao; Wu, Yining; Cheng, Rui; Zhao, Mingwei
Graphical abstract: In this work, we employed NMR technique to monitor the migration rule of nanofluid in sandstone cores during the spontaneous imbibition process. And EOR mechanism of the nanofluid was discussed. Highlights: A novel nanofluid based on functional silica nanoparticles was prepared. Imbibition and NMR measurement were combined to monitor oil distribution. 70.82–71.98 wt% of oil was distributed in mesopores (50 nm < pore size ≤ 3000  nm). The NMR spectra and imaging show that the nanoparticles seeped into the core. Abstract: Spontaneous imbibition of nanofluid has attracted much interest in enhanced oil recovery (EOR) in ultralow permeable reservoirs. However, the oil distribution in ultralow permeable cores during the spontaneous imbibition using nanofluids has not been discussed in detail. In this study, imbibition experiment and nuclear magnetic resonance (NMR) measurement were used to monitor the migration rule of nanofluid and oil distribution in the imbibition. The results show that 70.82–71.98 wt% of the oil was distributed in mesopores (50 nm < pore size ≤ 3000 nm). The final oil recoveries of cores immersed in different concentrations of nanofluids (0.1 wt%, 0.05 wt%, 0.01 wt%, and 0.005 wt%) and brine were 32.5%, 26.9%, 20.5%, 15.1%, and 8.3%, respectively. The NMR spectra and imaging show that the nanoparticles seeped into the core. Significant insight into the oil distribution during the imbibition of nanofluid is provided.